Analisis Strategi Peningkatan Daya Saing Madrasah Ibtidaiyah di Jember: Studi Multisitus - Mukniah,; Abidin, Zainal (TADRIS: Jurnal Pendidikan Islam, 2021)
Madrasas/schools that have certain advantages become choices, while those that are mediocre are increasingly being abandoned. In this situation, an effective madrasah competitive strategy will determine its competitiveness and survival. Based on this phenomenon, this study aims to uncover and find: (1) analysis of the internal and external environment of madrasas, and (2) strategies for increasing the competitiveness of madrasas. This research uses a case study type approach with a multi-site design. The research locus chosen was MI Ma'arif KH. Siddiq and MI Al-Hidayah Jember. Data collection techniques using interviews, observation, and documentation. The collected data is then analyzed simultaneously, both at single sites and across sites, with the following techniques: data reduction, data presentation, and drawing conclusions. All data were tested for validity through: feasibility test, transferability test, dependability test, and confirmability test. The results of this study find that first, the external environment of MI in the region faces a situation of intense competition because there are many SD/MI in the vicinity with a relatively close distance. Internally, MI is perceived as a formal educational institution oriented to religious education. However, each MI has its own uniqueness which is capitalized as a source of their respective advantages. Second, improving the competitive strategy chosen by MI is strengthening morals, accelerating Al-Qur'an learning, optimizing academic and non-academic achievements, and standardizing infrastructure.